Pengaruh Variasi Jenis Aktivator Asam dan Nilai Normalitas Pada Aktivasi Zeolit Pelet Perekat Terhadap Prestasi Mesin Motor Diesel 4-Langkah - Herry Wardono (JURNAL MECHANICAL, 2012)
The energy crisis and air pollution can be coped with using very abundant Natural Zeolites available in Indonesia, particularly in Lampung. Herry Wardono has applied the zeolite on petrol and diesel engines. In this applications, Lampung's natural zeolites can significantly save fuel consumption and reduce exhaust emissions of the engines. The best results occurred in the use of chemical-physical activated zeolite. All this time, chemical activator (acidic activator) used was H2SO4 0.2 N, and  other normalities of this acid have not been tested, as well as  other types of acidic activator. In this research, acidic activators used were H2SO4 and HCl which has a normality of 0.1 N, 0.2 N, 0.3 N and 0.5 N each. The amount of adhesive pelletized zeolite used was also variated, i.e 50, 100, and 150 grams. The results showed that the adhesive pelletized zeolite activated by HCl dominate the best results, with fuel consumption savings of 8.6472% and 10.3058% in the use of 100 and 150 grams of the zeolite. Meanwhile, the highest fuel consumption savings obtained in the use of adhesive pelletized zeolite activated by H2SO4 were  6.2992% and 7.8847%.Keywords: zeolit pelet perekat, oxygen- rich combustion, prestasi mesin diesel